Values mediated emotional adjustment by emotion regulation: A longitudinal study among adolescents in China - Liu, Ping; Mo, Bibo; Yang, Panpan; Li, Dan; Liu, Shihong; Cai, Dan (Frontiers in Psychology, 2023)
Values have a direct impact on adolescents’ mental health. However, its potential mediation mechanism has received little attention. A 1-year longitudinal survey design was used to investigate the mediating role of emotion regulation in the relationships between self-transcendence (vs. self-enhancement) values and emotional adjustment among adolescents. Participants were 863 senior school students from Shanghai and Qingdao, Shandong Province. Data on self-transcendence and self-enhancement values, loneliness, depression, and emotion regulation were collected at 2019 and 2020 by using self-report measures. The results showed that (1) adolescents’ endorsement with self-transcendence values decreased and self-enhancement values increased; adolescents in Shanghai had higher depression scores than that of adolescents in Qingdao; (2) emotion regulation only fully mediated the effect of self-transcendence values on loneliness; (3) not only the relationship between self-transcendence values and depression, but also the relationships between self-enhancement values and loneliness and depression were suppressed by emotion regulation. This study provides more evidence for the benefits of self-transcendence values and also sheds light on how to improve adolescents’ emotional adjustments.